Flipping the flipped: the co-creational classroom - Vuk Uskoković (The Asia-Pacific Society for Computers in Education (APSCE), 2018)
Abstract The flip teaching model is being increasingly adopted by higher education institutions as an active learning alternative to traditional lecturing. However, the flip model shares a number of critical premises with the classical didactics. The further flips of the flip are thus advocated and the fear of returning the method to its initial state, prior to the flip, via such flips of the flipped dispelled. Proposed here is a seminal variation to the flip model based on the active involvement of students in searching, finding, selecting, and assembling knowledge from various literature sources into the learning material for the entire class. Because students actively co-create the learning content together with other students and the instructor, one such open-ended collaborative model is christened "co-creational." Its conception and corollaries in relation to co-educational methods in general are discussed. The model is represented algorithmically, exemplified by a topic of choice and compared in a quasi-experimental setting against the standard flip and the traditional lecturing in a medical devices graduate class. Students were able to retain and reproduce the content covered using the co-creational pedagogic method better than using the standard flip or traditional lecturing. They also had a positive perception of the method, as compared to traditional lecturing. They did not have a preference for the co-creational method over the standard flip, but felt that they learned more using the co-creational method compared to the standard flip and that the co-creational model best prepared them for job searches in high-tech industry and academia. The co-creational model was also more open to the intrusion of moral instructions than traditional lecturing, going hand-in-hand with the community-building aspect of the ideal form of knowledge acquisition and creation.